(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2022)
Aim: Comparative efficacy analysis of laryngoscopes -Airtraq vs macintosh - using Intubation Time and Intubation difficulty score in simulated difficult airway using cervical collar. Methods: Peculiarity is simulated difficult airway by use of cervical collar. A prospective interventionalrandomized study conducted on 60 adult ASA grade-I&II patients scheduled for surgery in tertiary care center. Tracheal Intubation 1. Group(AVL) Airtraq videolaryngoscope (n=30) 2. Group(ML) Macintoshlaryngoscope (n=30). Parameters observed: 1) Intubation Time- seconds 2) Intubation Difficulty Score (IDS) comprised Numbers of-1. intubation attempts 2.operators 3.alternative intubation techniques, 4. Glottic exposure. 5. paramatric comparison lifting force required during laryngoscopy, Necessity for external laryngeal pressure, Position of the vocal cords. Results: With airtraq laryngoscope intubation discoursed outcomes intubation time is irrelevant with difficult airway where it is highly associated in case of macintosh laryngoscope. Intubation time & difficulty score is commentating use of Airtraq laryngoscope. Conclusions: The enhanced visual interiors expedite in such a way that intubation time in Airtraq is not dependent on IDS like Macintosh but on neuromuscular reflexes of performer, commentating the superiority of Airtraq over Macintosh